Fungsi, Kategori, dan Peran Sintaksis Menggunakan Teori RRG dalam Acara “Indonesia Lowyers Club” - Atika Gusriani; Zherry Putria Yanti; Lisa Yuniarti (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
The predicate is a determining element in a sentence. Sentences that are not clearly structured, result in the sentence being ineffective. This of course results in incomplete functions, categories, and roles in a sentence, making it difficult to understand. The purpose of this research is to describe functions, categories, and syntactic roles using the theory of Role and Reference Grammar (RRG) in the "Indonesia Lowyers Club" event. Distribution method is the main method used to analyze data. Before the data is selected based on its use, the data is recorded first. Furthermore, the data that has been collected is selected based on the needs of the indicators that have been set. The results of the research show that the function in syntax is filled by the components of subject, nucleus (core/predicate), object, and periphery (additional information). Categories in syntax are filled by components of nominal phrases (nouns), verbs (verbs), pronouns (pronouns), adjectives (adjectives), adverbs (adverbs), and clauses. The role in syntax is filled by the component agent (actor), predicate or nucleus indicating activity, and undergoer (patient/object).